Peran Pancasila Dalam Kemajuan Ilmu Pengetahuan Dan Teknologi - Fadhilah, Jihan; Usiono Usiono (Bersatu: Jurnal Pendidikan Bhinneka Tunggal Ika, 2024)
The role of Pancasila as a foundation for the development of science indicates that Pancasila acts as a basis and guide for the advancement of science and technology. Advances in science and technology have a significant impact on human life, and evolution in this field has the potential to change the world through machine innovations that facilitate various human activities. The purpose of this research is to outline the meaningfulness of the role of Pancasila in the advancement of science and technology. The research method applied is Systematic Literature Review (SLR). Data was collected by documenting all similar research articles in the research report. A total of 10 national journal articles were taken as samples from Google Scholar database for this research. The results of this study show the importance of having a deep understanding of how Pancasila has an important role in keeping up with the rapid development of science and technology.